COLOR BARS IN COMMUNICATION: संप्रेषण में रंगों की अठखेलियां - Srivastava, Rekha (International Journal of Research -GRANTHAALAYAH, 2014)
The expression of a person takes various forms in the journey from childhood to youth to middle age. Many elements intrude in this journey during its development and it is a kind of gratitude. Which happens not only in the life of man but also in the expression of the artist. Where every person discovers, expresses himself according to his thought streams. Develops its own value vision according to its own criteria. But in order to reach this stage, one has to constantly renounce excesses and live in the present in every form. It is most important for a painter to center himself on the elemental composition of the canvas, this path will take him where, beyond the nuances, he removes the essence of perfection and puts it on the white canvas. व्यक्ति की अभिव्यक्ति बचपन से लेकर जवानी फिर अधेड़ अवस्था तक के सफर में, विभिन्न रूप लेती है। इस यात्रा में बहुत सारे तत्व अपने विकास के दौरान घुसपैठ करते हैं और यह एक तरह का आभार है। जो सिर्फ मनुष्य के जीवन में ही नहीं घटता बल्कि कलाकार की अभिव्यक्ति में भी लक्षित होता है। जहां हर व्यक्ति अपनी विचार धाराओं के अनुरूप खुद को खोजता, व्यक्त करता है। खुद के मापदण्डों के अनुसार अपनी मूल्य दृष्टि विकसित करता हैै। परन्तु इस अवस्था तक पहुचने के लिये , व्यक्ति को लगातार अतिष्य का त्याग और हर रूप में मौजूदा वक्त में जीना होता है। एक चित्रकार के लिये कैनवास के तात्विक संयोजन पर खुद को केन्द्रित करना सबसे जरूरी है, यह रास्ता उसे ले जाएगा, जहां बारीकियों से परे वो पूर्णता का स्वत्व निकालकर सफेद कैनवास पर रख देता है।प